All-optical NOT and AND gates using nonlinear photonic crystal octagonal shape ring resonator - Gupta, Priyanka Kumari; Paltani, Punya Prasanna; Tripathi, Shrivishal (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
This paper proposes novel all-optical logic NOT and AND gates using an octagonal-shaped ring resonator with Kerr nonlinearity created on the platform of a two-dimensional photonic crystal (2DPC). The ring resonator offers maximum transmission efficiency and is simpler than the previously published designs. In our design, the nonlinearity is applied only to the outer rods of the core (rather than the whole core section) of the ring resonator, increasing their size. The proposed gates exhibit low operating and switching powers compared to the earlier proposals, which is highly desired for practically integrating any all-optical device.
Optica Applicata, Vol. 54, 2024, nr 4, s. 471-482
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; photonic crystals; all-optical logic gates; Kerr effect; FDTD